Use of peroral cholangiopancreatoscopy-assisted endoscopic mucosal resection for biliopancreatic intraductal lesions - Zhang, Wengang; Zhai, Yaqi; Shao, Bozong; Wang, Jiafeng; Wu, Qingzhen; Chai, Ningli; Linghu, Enqiang (Endoscopy, 2024)
Background This study aimed to assess the feasibility and safety of performing cholangiopancreatoscopy-assisted endoscopic mucosal resection (CA-EMR) for biliopancreatic intraductal lesions.Methods Special electrocautery snares and injection needles that can pass through the working channel of a single-operator cholangiopancreatoscope were developed. Between November 2023 and April 2024, we performed CA-EMR for two patients with gallbladder polyps, one patient with a neoplastic lesion in the common bile duct (CBD), and one patient with a neoplastic lesion in the main pancreatic duct. The technical success rate and adverse events were recorded.Results All four CA-EMR procedures were performed successfully. Postoperative pathology revealed inflammatory gallbladder polyps in two patients, low grade intraepithelial neoplasia of the CBD in one patient, and intraductal papillary mucinous neoplasm (IPMN) in one patient. The patient with IPMN experienced mild postoperative pancreatitis and recovered after conservative treatment. No adverse events were encountered in the other three CA-EMR procedures.Conclusion This study preliminarily confirmed the feasibility and safety of CA-EMR for treating biliopancreatic intraductal lesions.